Placing the place in employer branding : The case of the tourism and hospitality sector in Northern Sweden - Ek Styvén, Maria; Näppä, Anna; Parding, Karolina (Luleå tekniska universitet, Industriell ekonomi, 2023)
Employment value proposition in the tourism and hospitality industry